Carborane and cyanine conjugated galactose targeted amphiphilic copolymers for potential near infrared imaging-guided boron neutron capture therapy (BNCT). Issue 12 (13th August 2018) - Ruan, Zheng; Yuan, Pan; Liu, Le; Xing, Tao; Yan, Lifeng
ABSTRACT: Near infrared fluorescent galactose targeted glycopolymer containing m -carborane has been synthesized through ring open and atom transfer radical polymerization, followed by post-functionalization with a cyanine NIR dye. The copolymer could self-assemble into micelles which work as a potential agent for imaging-guided boron neutron capture therapy. The NIR micelles revealed no cytotoxicity for HepG2 cells. An enhanced and fast endocytosis due to the specific interaction between the HepG2 cells and the glycopolymer could be traced by fluorescence microscopy, and the bioimaging makes it possible to trace the nanoparticles and provides information where and when the neutron irradiation should be triggered. GRAPHICAL ABSTRACT: